Methodology for Establishing a Population-Based Birth Cohort Focusing on Couple Fertility and Children’s Development, the Upstate KIDS Study - Buck Louis, Germaine M. (Paediatr Perinat Epidemiol, 2014)
BACKGROUND: Critical data gaps remain regarding infertility treatment and child development. We assessed the utility of a birth certificate registry for developing a population cohort aimed at answering such questions. METHODS: We utilized the Upstate New York live birth registry (N=201,063) to select births conceived with (n=4,024) infertility treatment or exposed infants, who were then frequency-matched by residence and plurality to a random sample of infants conceived without (n=14,455) treatment or unexposed infants, 2008–2010. Mothers were recruited at 2–4 months postpartum and queried about their reproductive histories including infertility treatment for comparison with birth certificate data. Overall, 1,297 (32%) mothers of exposed and 3,692 of unexposed (26%) infants enrolled. RESULTS: Twins represented 22% of each infant group. The percentage of infants conceived with/without infertility treatment was similar whether derived from the birth registry or maternal report: 71% none, 16% drugs or intrauterine insemination, and 14% ART. Concordant reporting between the two data sources was 93% for no treatment, 88% for ART and 83% for fertility drugs, but differed by plurality. Exposed infants had slightly (p<0.01) earlier gestations than unexposed infants (38.3±2.8 and 38.7±2.7 weeks, respectively) based upon birth certificates but not maternal report (38.7±2.7 and 38.7±2.9, respectively). Conversely, mean birthweight was comparable using birth certificates (3157±704 and 3194±679 grams, respectively), but differed using maternal report (3167±692 and 3224±661, respectively p<0.05). CONCLUSIONS: The birth certificate registry is a suitable sampling framework as measured by concordance with maternally reported infertility treatment. Future efforts should address the impact of factors associated with discordant reporting on research findings.